What I wanted and what I did: Motivation and engagement in a massive open online course - Anghel, Ella; Littenberg-Tobias, Joshua; von Davier, Matthias (Computers and education, 2023)
Existing studies on MOOCs examine learners’ engagement processes but have not explored links between them and motivations to enroll. In our previous work, we identified three motivation groups in a MOOC for educators: intrinsic, professional, and prosocial. In the current study, we used process mining to compare the course engagement patterns of these three groups. We found that throughout the course, the intrinsic group was the most engaged, but the prosocial group became the most engaged by the end of the course. We also identified rarely visited pages and page sequences that do not follow the intended course structure. Our findings enhance existing research on motivation and engagement in MOOCs by showing how motivation relates to fine-grained engagement metrics. They suggest that MOOC developers may want to consider why some groups are less engaged and why some pages appear less engaging and change the course structure accordingly. •We explored the engagement patterns of learners in a massive open online course•Learners with intrinsic, professional, and prosocial motivations were compared•Intrinsic motivation was associated with higher engagement overall•Prosocial learners were more engaged at the end of the course•We identified sequences of page visits that do not follow the intended structure